Fip1 Regulates the Activity of Poly(A) Polymerase through Multiple Interactions - Helmling, Steffen (American Society for Microbiology, 2001)
Fip1 is an essential component of the Saccharomyces cerevisiae polyadenylation machinery and the only protein known to interact directly with poly(A) polymerase (Pap1). Its association with Pap1 inhibits the extension of an oligo(A) primer by limiting access of the RNA substrate to the C-terminal RNA binding domain (C-RBD) of Pap1. We present here the identification of separate functional domains of Fip1. Amino acids 80 to 105 are required for binding to Pap1 and for the inhibition of Pap1 activity. This region is also essential for viability, suggesting that Fip1-mediated repression of Pap1 has a crucial physiological function. Amino acids 206 to 220 of Fip1 are needed for the interaction with the Yth1 subunit of the complex and for specific polyadenylation of the cleaved mRNA precursor. A third domain within amino acids 105 to 206 helps to limit RNA binding at the C-RBD of Pap1. Our data demonstrate that the C terminus of Fip1 is required to relieve the Fip1-mediated repression of Pap1 in specific polyadenylation. In the absence of this domain, Pap1 remains in an inhibited state. These findings show that Fip1 has a crucial regulatory function in the polyadenylation reaction by controlling the activity of poly(A) tail synthesis through multiple interactions within the polyadenylation complex.